Albanian Diaspora in Greece in the years 1990-2000 - Kadzadej, Mustafa; Hoxha, Kleviona (European Journal of Multidisciplinary Studies, 2016)
The reasons that prompted the Albanian exodus were numerous and varied. While if we take a look on its consequences will see that they have a dual nature. Among the positive aspects of exodus we can mention the fact that it helped Albania economically meeting the needs of a considerable part of the population in the moment of political and social crisis transition enabling the survival of many families. On the other hand it had a negative impact not only becouse of spending vital energies of the nation abroad, but also because it led to the formation of a bad opinion about Albanians, opinion spread almost all over Europe, especially where their presence was bigger. For this reason we got to study precisely the image of immigrant in two countries ( Italy and Greece ), where they have the largest flow of migration in 1990-2000. We should note that in recent years in both countryes in Italy and in Greece prevails the same closed mentality against foreigners. Also it is accompanied ( especially in Italy with the malfunctioning of the structure that handles issues of migratory movements, not like in the other states like Germany, England or France where, besides the small number of immigrants, there were laws and better functioning of the state that associated with emigration’s problems. On the other hand we can say that in this period, whether in Greece the fortunes of the Albanian immigrants depended from the relations of the Greek-Albanian state, in Italy they depend mainly on the behavior of immigrants.
Keywords: Albanian diaspora,Greece